Réponses

Meilleure réponse !
2014-05-27T13:58:54+02:00
(x+1)²=(2x+1)(x+1)
x²+2x+1=2x²+2x+x+1
x²+2x+1-2x²-3x-1=0
-x²-x=0
x(-x-1)=0
x=0
-x-1=0
x=-1
2)
x+2=x²+4x+4
x+2=(x+2)²
x+2-(x+2)²=0
(x+2)(1-x-2)
x+2=0
x=-2
-x-1=0
x=-1
3)
(x+1)²=9x²
(x+1)²-9x²=0
(x+1)²-(3x)²=0
(x+1-3x)(x+1+3x)=0
(-2x+1)(4x+1)=0
-2x+1=0
-2x=-1
x=1/2
4x+1=0
x=-1/4
4)
(6x-2)(x+1)=9x²-6x+1
(6x-2(x+1)=(3x-1)²
2(3x-1)(x+1)-(3x-1)²=0
(3x-1)[2(x+1)-(3x-1)]=0
3x-1=0
x=1/3
2x+2-3x+1=0
-x+3=0
x=3
5)
(x-1)(2x+3)-2x+2=0
(x-1)(2x+3)-2(x-1)=0
(x-1)(2x+3-2)=0
(x-1)(2x+1)=0
x-1=0
x=1
2x+1=0
x=-1/2